2018
DOI: 10.1002/ajp.22875
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin‐ and arginine vasopressin‐containing fibers in the cortex of humans, chimpanzees, and rhesus macaques

Abstract: Oxytocin (OT) and arginine-vasopressin (AVP) are involved in the regulation of complex social behaviors across a wide range of taxa. Despite this, little is known about the neuroanatomy of the OT and AVP systems in most non-human primates, and less in humans. The effects of OT and AVP on social behavior, including aggression, mating, and parental behavior, may be mediated primarily by the extensive connections of OT- and AVP-producing neurons located in the hypothalamus with the basal forebrain and amygdala, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 71 publications
3
30
0
Order By: Relevance
“…In contrast, the DupB+/− chimpanzees show lesser gray matter covariation than DupB−/− chimpanzees in regions comprising component 6, including the superior temporal sulcus and the postcentral sulcus. These regional differences overlap with brain regions previously found to differ in vasopressin and oxytocin neural fibers between nonhuman primates, and in AVPR1A gene expression in humans with different RS3 alleles (cingulate, insula and the hippocampus) . Moreover, several of the larger regions identified in components 4‐6 overlap with those that comprise the social brain network (prefrontal cortex, insula, cingulate and superior temporal sulcus), which is consistent with our hypothesis that these polymorphisms affect brain structures inolved in regulation of social cognition and behavior.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In contrast, the DupB+/− chimpanzees show lesser gray matter covariation than DupB−/− chimpanzees in regions comprising component 6, including the superior temporal sulcus and the postcentral sulcus. These regional differences overlap with brain regions previously found to differ in vasopressin and oxytocin neural fibers between nonhuman primates, and in AVPR1A gene expression in humans with different RS3 alleles (cingulate, insula and the hippocampus) . Moreover, several of the larger regions identified in components 4‐6 overlap with those that comprise the social brain network (prefrontal cortex, insula, cingulate and superior temporal sulcus), which is consistent with our hypothesis that these polymorphisms affect brain structures inolved in regulation of social cognition and behavior.…”
Section: Discussionsupporting
confidence: 90%
“…In humans, variation in RS3 is related to activation of the amygdala during a face recognition task, an observation that supports the amygdala theory of autism . Immunohistochemistry analyses have revealed species similarities and differences in both oxytocin and vasopressin fibers in regions of the human, chimpanzee and rhesus macaque cortex . With respect to vasopressin, fibers were found in the anterior olfactory nucleus, primary olfactory cortex and subgenual region of the anterior cingulate cortex of all three species.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…In this area, its anxiolytic activity is brought about by the recruitment of an oxytocin receptor (OTR)-TRPV2 channels (and subsequent Ca2+ influx)-MEK1/2 pathway (van den Burg et al 2015). Underlying mechanisms of oxytocin and fear extinction in other brain regions, like the PFC and amygdala, are beginning to be explored, motivated by the discovery of OT release and OTR expression in those areas (Knobloch et al 2012;Mitre et al 2016;Li et al 2016;Rogers et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…While there are some key differences, there is also overlap in OXTR expression concentrations in the CNS across species (Insel, 2010), including non-human primates (Freeman and Young, 2016). Rogers et al (2018), for example, found OT immunoreactive fibers in the straight gyrus of the orbitofrontal cortex and anterior cingulate gyrus, a region involved in pain processing, in both humans and chimpanzees, but not macaques. Immunohistological investigation of the ventral hypothalamus of the macaque showed the presence of OXTR in the septal nucleus and preoptic area (Boccia et al, 2001).…”
Section: Central Nervous Oxytocin Binding Sitesmentioning
confidence: 99%